2021
DOI: 10.1002/cam4.4135
|View full text |Cite
|
Sign up to set email alerts
|

LungBEAM: A prospective multicenter study to monitor stage IV NSCLC patients with EGFR mutations using BEAMing technology

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…The mutant allele dynamics of T790M and the major activating mutations were expected to be identical. The dynamics of ctDNA, especially the disappearance of mutant alleles after the introduction of osimertinib, have been reported to predict long-term efficacy 35 37 . Consistent with this result, in the present study, we observed a trend toward a longer response to osimertinib in patients showing early disappearance of T790M and major activating mutation alleles; however, the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…The mutant allele dynamics of T790M and the major activating mutations were expected to be identical. The dynamics of ctDNA, especially the disappearance of mutant alleles after the introduction of osimertinib, have been reported to predict long-term efficacy 35 37 . Consistent with this result, in the present study, we observed a trend toward a longer response to osimertinib in patients showing early disappearance of T790M and major activating mutation alleles; however, the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…LungBEAM, a prospective study across 19 Spanish hospitals, collected serial blood specimens at baseline from 110 treatment-naïve patients with advanced EGFR -mutant NSCLC and monthly for EGFR T790M emergence while on first-line EGFR TKI therapy until radiographic progression [ 90 ]. Progression was observed in 68 of the 110 patients (61.8%) who completed the study.…”
Section: Treatment Response Monitoringmentioning
confidence: 99%
“…Progression was observed in 68 of the 110 patients (61.8%) who completed the study. Twenty-six patients (23.6%) showed the presence of an EGFR T790M mutation in plasma, with detection at a median of 76 days prior to radiographic progression [ 90 ].…”
Section: Treatment Response Monitoringmentioning
confidence: 99%
“…The DNA can then be released from the beads and analyzed with flow cytometry or optical scanning instruments to locate mutation ( 16 , 17 ). A recent LungBEAM study demonstrated the great potential of BEAMing in optimizing treatment in patients with advanced NSCLC ( 18 ).…”
Section: Introductionmentioning
confidence: 99%